Vitamin D status rosk factors among stroke patients in a tertiary neurological center in Kathmandu. - Chandra,Avinash
ABSTRACT: Anxiety disorders are common among hospitalized patient. The co-existence of these disorders are associated with barriers to treatment and worsening medical outcomes. Anxiety disorder is amongst the most common psychiatric disorders in all over the world. Emerging evidence suggests that anxiety and the anxiety disorders, which have received relatively less attention and many patients have co morbid anxiety symptoms, which are associated with increased severity of psychiatric illness, additive functional impairment and medical costs and also amplify symptoms of some medical illnesses and appear to worsen clinical outcomes. Patients with chronic conditions like neurological and neurosurgical disease may experience many negative emotions during hospital staywhich increase their risk for the development of mental health disorders particularly anxiety. Our study is a hospital based cross sectional study which aims to find out the prevalence of anxiety among hospitalized patient and the correlates of the same . A self administered questionnaire including various variables which may relate to anxiety was administered to the patients admitted in hospital . The standard questionnaire including Hospital Anxiety Scale, AUDIT and Fragesterum Questionnaire was also used to find out the anxiety and its associated factors. Present study reveals that 174 among 260 participants (66.9%) were found to have anxiety by Hospital Anxiety Scale. anxiety was found to be statistically significant with age of the participant. (OR=0.333 CI= 0.192-0.579). Also, participants who had at least one chronic disease were found to have anxiety two times more likely than those who do not have any chronic illness and this association was found to be statistically significant (OR=2.034 CI=1.141-3.626) This study found prevalence of high anxiety. The need for a focused approach to mental health care within the hospital has been discussed for a long time. The study concluded to improve the patient care especially to address mental health of the patient within hospital with a friendly environment making better relationship of patient and healthcare staffs.